PENGARUH PESAN PERSUASIF PADA KAMPANYE "MY BODY IS PERFECT AND I LOVE IT" TERHADAP KEPERCAYAAN DIRI PEREMPUAN - Bunga Febriana (2022)
One of the campaigns that currently has been going on on social media is a campaign related to self-love created by Marshanda. The campaign, entitled "My Body is Perfect and I Love It" contains a persuasive message about a phenomenon that still often occurs in society, for example, the lack of confidence in women about their body shape. With this self-love campaign, it is hoped that the community will understand the importance of accepting the condition of their body. The method used in this research is quantitative explanatory with a survey method conducted by distributing questionnaires using Google Forms to 400 respondents who are subscribers to the MARSHED Youtube channel and have watched the campaign video "My Body is Perfect and I Love It". The sampling technique used is non-probability with the purposive sampling method. The Elaboration Likelihood Model will serve as a guide in this research to measure the effect of persuasive messages in the "My Body is Perfect and I Love It" campaign on women's self-confidence by looking at how the audience of the campaign elaborates the message to the stage of changing attitudes as expected. The results obtained from this study indicate that there is a significant effect between persuasive messages in the "My Body is Perfect and I Love It" campaign on women's self-confidence.